METACOGNITION OF YEAR 12 PACKAGE C LEARNERS ON PERMUTATION - Puadah, Peni Fauziah; Suhendra, Suhendra; Hidayat, Angga (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
One of the levels in the thinking process that students can use to solve problems is metacognition. Metacognition encourages students to realize and control their thinking process. Metacognition skills are needed to support students' independent learning process, one of which is in the learning process carried out in the Equivalency Education program. This study aims to describe the metacognition skills of Year 12 students on permutation and combination. This descriptive qualitative research was conducted at a Community Learning Center in Bandung, involving 12 subjects. The instruments used in this study were metacognition tests, questionnaires, and interviews. The results showed that students with high Mathematics Initial Ability had metacognition knowledge with reflective use and strategic use levels. Learning citizens with medium initial mathematical ability have metacognition knowledge with strategic use level, and learning citizens with low initial mathematical ability are at the aware use metacognition knowledge level. In the indicator of metacognition skills, learning citizens with high initial mathematics abilities are at the strategic use level, learning citizens with moderate initial mathematical ability categories are at the strategic use level, and aware use, learning citizens with low initial mathematical ability categories are at the tacit use level. In general, the metacognitive abilities of learning citizens in the high, medium, and low initial mathematical categories are at the strategic use, aware use.